Development of a Syrian hamster anti-PD-L1 monoclonal antibody enables oncolytic adenoviral immunotherapy modelling in an immunocompetent virus replication permissive setting - Clubb, James H. A.; Kudling, Tatiana V.; Girych, Mykhailo; Haybout, Lyna; Pakola, Santeri; Hamdan, Firas; Cervera-Carrascon, Víctor; Hemmes, Annabrita; Grönberg-Vähä-Koskela, Susanna; Santos, João Manuel; Quixabeira, Dafne C. A.; Basnet, Saru; et al. (Frontiers in Immunology, 2023)
Introduction Immune checkpoint inhibitors (ICIs) have revolutionized the treatment of cancer, but preclinical testing of hypotheses such as combination therapies has been complicated, in part due to species incompatibility issues. For example, one of few known permissive animal models for oncolytic adenoviruses is the Syrian hamster, for which an ICI, mainly an anti-PD-L1 monoclonal antibody (mAb) was not previously available. In this study, we developed an anti-Syrian hamster PD-L1 mAb to enable the evaluation of safety and efficacy, when combining anti-PD-L1 with an oncolytic adenovirus encoding tumour necrosis factor alpha (TNFα) and interleukin-2 (IL-2) (Ad5/3-E2F-D24-hTNFα-IRES-hIL-2 or TILT-123). Methods Recombinant Syrian hamster PD-L1 was expressed and mice immunized for mAb formation using hybridoma technology. Clonal selection through binding and functional studies in vitro, in silico and in vivo identified anti-PD-L1 clone 11B12-1 as the primary mAb candidate for immunotherapy modelling. The oncolytic virus (OV) and ICI combination approach was then evaluated using 11B12-1 and TILT-123 in a Syrian hamster model of pancreatic ductal adenocarcinoma (PDAC). Results Supernatants from hybridoma parent subclone 11B12B4 provided the highest positive PD-L1 signal, on Syrian hamster PBMCs and three cancer cell lines (HT100, HapT1 and HCPC1). In vitro co-cultures revealed superior immune modulated profiles of cell line matched HT100 tumour infiltrating lymphocytes when using subclones of 7G2, 11B12 and 12F1. Epitope binning and epitope prediction using AlphaFold2 and ColabFold revealed two distinct functional epitopes for clone 11B12-1 and 12F1-1. Treatment of Syrian hamsters bearing HapT1 tumours, with 11B12-1 induced significantly better (p<0.05) tumour growth control than isotype control by day 12. 12F1-1 did not induce significant tumour growth control. The combination of 11B12-1 with oncolytic adenovirus TILT-123 improved tumour growth control further, when compared to monotherapy (p<0.05) by day 26. Conclusions Novel Syrian hamster anti-PD-L1 clone 11B12-1 induces tumour growth control in a hamster model of PDAC. Combining 11B12-1 with oncolytic adenovirus TILT-123 improves tumour growth control further and demonstrates good safety and toxicity profiles.